Strategic accounting in the context of transition to a circular economy model - Semaniuk, Vita; Bandurka, Maksym (Herald of Economics, 2025)
Introduction. In the context of global environmental challenges and the increasing scarcity of natural resources, the transformation of contemporary economic systems towards a circular economy acquires particular significance. The circular economy involves creating closed loops of material flows, regeneration of natural resources, and minimization of waste. At the same time, this transition significantly influences traditional approaches to managerial and strategic accounting, necessitating the integration of financial and non- financial metrics, including environmental and social indicators.Purpose of the study. Substantiation of the role of strategic accounting as a key source of information for managing enterprises during the transition to a circular business model, as well as identifying environmental and economic information as an essential resource for strategic decision-making in the field of environmental economics.Research methods. Bibliometric analysis of scientific publications, methods of comparison, critical analysis, and conceptual generalization.Results. It has been established that the circular economy, contrasting itself with the linear model, is based on closed material cycles, regeneration of natural resources, and waste minimization. It has been proven that strategic accounting in the new economic paradigm should integrate financial and non-financial metrics (carbon footprint, material intensity, circularity indicators), thereby facilitating effective managerial decision-making.Prospects. Development of unified methods of strategic accounting using digital technologies.